2022
DOI: 10.31083/j.jomh1809179
|View full text |Cite
|
Sign up to set email alerts
|

Men’s mental health during the COVID-19 pandemic: a scoping review

Abstract: Background: Mental health issues can be more severe in men vulnerable to isolation and loneliness during a pandemic because of social distancing and isolation measures. The purpose of this study was to identify current research trends and the impact of the coronavirus disease (COVID-19) on men's mental health through a scoping review, and to make recommendations for improvements. Methods: This study conducted a scoping review to explore and analyze research trends on the effect of COVID-19 on men's mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Specifically, the study sample primarily consisted of White women of high socioeconomic status and thus, the mental health of Ontario adults of different genders, ethnicities, and low socioeconomic status is largely unknown. This information is important, especially considering international researchers have found that the COVID-19 pandemic has negatively impacted the mental health of men (Park & Yu, 2022), sexual and gender minority populations (Moore et al, 2021), and ethnic minorities (Smith et al, 2020), with minority populations being disproportionately affected (Moore et al, 2021). Moreover, Chung et al (2021) explored whether the mental health and wellbeing of adults who were socioeconomically disadvantaged was worse than those of high socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the study sample primarily consisted of White women of high socioeconomic status and thus, the mental health of Ontario adults of different genders, ethnicities, and low socioeconomic status is largely unknown. This information is important, especially considering international researchers have found that the COVID-19 pandemic has negatively impacted the mental health of men (Park & Yu, 2022), sexual and gender minority populations (Moore et al, 2021), and ethnic minorities (Smith et al, 2020), with minority populations being disproportionately affected (Moore et al, 2021). Moreover, Chung et al (2021) explored whether the mental health and wellbeing of adults who were socioeconomically disadvantaged was worse than those of high socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Individual, interpersonal and contextual factors, such as intolerance of uncertainty, emotion regulation, poor or lack of social support, isolation, financial stressors and increasing unemployment rates (Ellison et al, 2021; Palma, de Sousa, et al, 2022; Palma, Sousa, et al, 2022; Park & Yu, 2022) might lead to greater psychological suffering in men. For example, Park and Yu (2022) highlighted that isolation and loneliness severely impacted men’s mental health during the COVID‐19 pandemic. Further, they observed an increase in studies dealing with men's adverse mental health outcomes, such as depression, anxiety, insomnia and use of substances (e.g., alcohol and tobacco).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several determinants of men's psychological distress have been reported over the last 2 years (Palma, de Sousa, et al, 2022; Palma, Sousa, et al, 2022; Park & Yu, 2022). For instance, common mental disorders (i.e., indicators of anxiety, depression and stress‐related disorders) and perceived stress (i.e., individuals' appraisal of life stressors and their ability to cope with them effectively) have been consistently associated with intraindividual (e.g., intolerance of uncertainty, emotion regulation and coping strategies) and contextual (e.g., socio‐economic status, monthly income and marital status) variables, to varying degrees (Palma, de Sousa, et al, 2022; Palma, Sousa, et al, 2022; Park & Yu, 2022). However, the processes that might help protect individuals against psychological distress in the COVID‐19 context still warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations